2009
DOI: 10.1007/s12032-009-9167-2
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of human kallikrein 11 is associated with poor prognosis in patients with low rectal carcinoma

Abstract: hK11 may be another prognostic biomarker of LRC. Knowledge of hK11 expression in LRC tissues could contribute to the prediction of prognosis of LRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
9
0
2
Order By: Relevance
“…Associated with cirrhosis and hepatitis C virus (HCV) infection; inversely associated with hepatitis B virus (HBV) infection ing Dukes' staging, histologic grade, CEA levels, lymph node metastasis, and invasion depth. In fact, weak KLK11 expression predicted a better clinical outcome for low rectal carcinoma patients (38).…”
Section: Association Of Klk Gene Expression With Clinico-pathologicalmentioning
confidence: 99%
“…Associated with cirrhosis and hepatitis C virus (HCV) infection; inversely associated with hepatitis B virus (HBV) infection ing Dukes' staging, histologic grade, CEA levels, lymph node metastasis, and invasion depth. In fact, weak KLK11 expression predicted a better clinical outcome for low rectal carcinoma patients (38).…”
Section: Association Of Klk Gene Expression With Clinico-pathologicalmentioning
confidence: 99%
“…Kallikrein-related peptidases 11 (KLK11) is a member of the human kallikrein gene family, which localized on chromosome 19q13.4 [5]. Recent studies have reported that KLK11 has been expressed in many cancers, including prostate cancer [6], ovarian cancer [7], gastric cancer [8], as well as rectal carcinoma [9]. An immunofluorometric assay study demonstrated that KLK11 expression in ovarian cancer tissues is a marker of favorable prognosis, since patients with KLK-positive tumors exhibit a longer progression-free survival (PFS) and overall survival (OS) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Serine proteases play a role in cascade pathways, such as the blood coagulation cascade, the dissolution of blood clots, the intestinal digestive enzymes, and the apoptosis pathway [ 6 ]. Kallikrein cascade seems to be valuable in elucidation of the various mechanisms underlying cancer invasion and metastasis [ 9 ]. There is evidence of a link between kallikreins and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an association between kallikreins and cancer prognosis. Yu et al [ 9 ] reported that over-expression of hK11 was associated with poor prognosis in patients with low rectal carcinoma. Diamandis et al [ 11 ] found that hk11 is an indicator of favorable prognosis in ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%